2015
DOI: 10.18632/oncotarget.6003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of skin cancer by correlation and complexity analyses of damaged DNA

Abstract: Skin cancer is a common, low-grade cancerous (malignant) growth of the skin. It starts from cells that begin as normal skin cells and transform into those with the potential to reproduce in an out-of-control manner. Cancer develops when DNA, the molecule found in cells that encodes genetic information, becomes damaged and the body cannot repair the damage. A DNA walk of a genome represents how the frequency of each nucleotide of a pairing nucleotide couple changes locally. In this research in order to diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Although, in medical science, fractal properties have been reported for various cases such as DNA2, Blood vessel and pulmonary vessels3, heart sound4, heart rate5, EEG signal6, bone structure7 and human stride time series8, there have been limited works which analyzed the fractal dynamics of eye movements as a random walk. Besides some works which found out the fractal nature of fixational eye movements910, some scientists have worked on analysis of eye movements in healthy or unhealthy subjects.…”
mentioning
confidence: 99%
“…Although, in medical science, fractal properties have been reported for various cases such as DNA2, Blood vessel and pulmonary vessels3, heart sound4, heart rate5, EEG signal6, bone structure7 and human stride time series8, there have been limited works which analyzed the fractal dynamics of eye movements as a random walk. Besides some works which found out the fractal nature of fixational eye movements910, some scientists have worked on analysis of eye movements in healthy or unhealthy subjects.…”
mentioning
confidence: 99%
“…DNA walk as a fractal random walk shows the variations of purine-pyrimidine displacement along nucleotide distance. In (27) we showed that variations of DNA affect its DNA walk's fractal dimension. Then, in order to study the DNA walk and human face, we considered the complexity phenomenon and used fractal dimension.…”
Section: Methodsmentioning
confidence: 99%
“…In an extensive work on analysis of fractal dimension of face according to the age, Yarlagadda et al developed a method that classified facial images into four categories i.e. child image [0][1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], young adult image [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], middle-aged adult image [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], and senior adult image (> 50) based on correlation fractal dimension value of a facial edge image (21...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the question, which arises here, is that how we can One useful approach to study the scaling properties of many biological time series is to apply methods derived from the concept of selfsimilar (fractal) processes [4][5][6]. A fractal is a natural phenomenon or a mathematical set that exhibits a repeating pattern that displays at every scale [7].…”
mentioning
confidence: 99%